USING UNSCRIPTED ROLE-PLAY TEACHING ACTIVITY TO IMPROVE STUDENTS’ SPEAKING ABILITY - Rufina Wilda Toding; Muhammad Yahrif; Suharti Sirajuddin (IKIP Siliwangi, 2021)
In learning English, most of the students think that English is a difficult skill. Given that, the writers want to improve the students’ speaking skills in English by using the Unscripted Role Play Teaching Activity. The data from classroom action research is collected by quantitative data (oral test) as main data and qualitative data (notes and documentation) as supporting data. The outcomes show that students have improved in English. It proves by ab average score that the students achieved in cycle 1 and cycle 2. In Cycle 1, the average score was 63.28 with 11 students (31.42%) achieved the standard minimum score whilst the average score in Cycle 2 is 78,28 with 30 students (80.71%) achieved the standard minimum score. In conclusion, the unscripted role-play teaching activity has improved the students’ speaking ability. Keywords: Unscripted, Role Play, Language Competence